PENENTUAN KAFEIN SECARA AMPEROMETRI DENYUT MENGGUNAKAN ELEKTRODA KARBON SCREEN-PRINTED - Setyorini, Dian Ayu; Mulyasuryani, Ani; Fardiyah, Qonitah (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Caffeine is usually used as an additive in drinks, foods and medicines. Caffeine has a negative effect on the human body so ithas a limited dose to consume. Amperometric detection can be used to measure caffeine by using SPCE. Determination of caffeine by amperometry can use single-pulse (SPA) and double-pulse (DPA). SPA applied detection potential 1,3 V (0,05 s) and has limit of detection 22 µM. DPA applied detection potential 1,3 V (0,05 s) and cleaning potential 0,35 V (0,1 s) and has limit of detection 0,9 µM. DPA was used to measure caffeine in sample of energy drinks and it concludes good accuracy. Keywords: pulse amperometry, caffeine, SPCE.